“Pakaian Syar’i” dalam Perspektif Maqashid Al-Syariah - Fauzi Yati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
Maqashid al-Syariah is part of the study of Islamic law to find out the purpose and wisdom of the commands and prohibitions of Islamic law. So that the human mind not only believes in the truth of revelation through the Qur'an and Sunnah, but can also understand the values of maslahat for life. Basically, maqasid al-syariah requires Muslim women to cover the aurat is one way to protect it. Therefore, clothing becomes a way for a woman to cover her aurat. However, there are characteristics of women's clothing that is hated by Allah SWT and Rasulullah SAW is clothing that seems excessive. The attitude of exceeding limits or exaggeration in religion is called ghuluw. Wearing excessive clothing while riding a motorcycle will cause the maqashid al-syariah not to be maintained, such as: hifdz al-nafs, hifdz al-aql, hifdz an-nasl, and hifdz al-mal, because excessive clothing while riding a motorcycle can cause danger for several reasons, such as: interference with concentration; potentially can be squeezed on the engine or motorcycle wheels; risk of falling or falling; interference with visibility; potential for wind; and danger on the route and road conditions.